Studies of III-V ferromagnetic semiconductors - Wang, Mu (2012)
The III-V ferromagnetic semiconductor Gallium Manganese Arsenide ((Ga,Mn)As) is one of the most interesting and well studied materials in spintronics research area. The first chapter is a brief introduction to spintronics, the properties of (Ga,Mn)As and the growth technique molecular beam epitaxy (MBE). Then the thesis presents a detailed study of the effect on the Curie temperature (TC) of varying the growth conditions and post-growth annealing procedures for epitaxially grown (Ga,Mn)As materials. The results indicate that it is necessary to optimize the growth parameters and post-growth annealing procedure to obtain the highest TC. From detailed magnetotransport studies, the carrier densities of high TC (Ga,Mn)As and H-doped (Ga,Mn)As have been achieved. It is found that the anomalous Hall resistance is the dominant contribution even at room temperature for these samples, which means it is incorrect to obtain carrier densities directly from Hall slope at high temperature. The results also show that the as-grown and lightly annealed H-doped (Ga,Mn)As samples have relatively high Curie temperatures down to low carrier density which make them good candidates for showing strong gate control of ferromagnetism.